Pengenalan Pendidikan Seni Tari Pada Anak Taman Kanak-Kanak - Fuji Astuti (FBS Universitas Negeri Padang, 2021)
The limitations of kindergarten teachers, who generally do not have an art education background, are not a barrier to not teaching dance to kindergarten children, because learning the art of dance in kindergarten children is prioritized on how teachers can motivate students to be able to carry out locomotor movements with confidence that can be done while playing. Based on the results of the training provided to kindergarten teachers throughout the district. Pasaman Barat is able to organize simple dances and can be taught to kindergarten children according to the level of difficulty and characteristics of kindergarten children. In this training, teachers are trained to explore and imitate movements according to the level of understanding and abilities of kindergarten children as objects that are used as a source of expression for expressive movements for students. The technique used during the training is the group method. In each group, the teacher identifies the characteristic tendencies of the students, which then after getting the ideas, then the ideas and ideas are developed in a theme as the basis for constructing a series of dance moves so that they become a dance repertoire that is ready to be taught to kindergarten children. Thus the dance that is taught to kindergarten children can be done by class teachers even though they do not have a background in dance education. The dance that is taught can be felt by students, because the material provided is adjusted to the level of difficulty and characteristics of the child. Furthermore, dance learning in kindergarten children is more aimed at exploring the potential that exists in children through the process of exploration and imitation so as to give birth to expressive movements according to the level of understanding carried out while playing in a pleasant atmosphere.